The Impact Of Covenant University Micro Finance Bank On Small Businesses In OTA And ENVIRONS - Chiazor, I. A; Jegede, A.; Ozoya, M. I.; Adebayo, M. (Advances in Social Sciences Research Journal, 2018)
This study assessed the impact made by Covenant Microfinance Bank (CMFB ) on Small Scale Businesses in Ota and its environs since inception. The immediate objective of this research was to examine how CMFB have impacted the lives of Small Scale Businesses through the Micro-credit loans it gives to these categories of persons who are generally regarded as the poor in Ota community and its environs. Survey method was employed in this study. Copies of questionnaire were administered to respondents systematically selected from the list of CMFB loan beneficiaries. They consist of petty traders, farmers, artisan, okada riders (Commercial Bike Riders), hair dressers and suppliers. The loans given out by CMFB served as take-off capital that is generally regarded as a crucial tool in alleviating poverty among the poor segment of every community. Findings from this study show that majority of the respondents have been empowered and lifted from poverty, as they were able to utilize the microcredit they obtained from the Bank in expanding their businesses. Thus establishing the fact that micro-financing is a powerful tool for poverty alleviation. It is the view of the researchers that further studies be undertaken to assess CMFB impact on other categories of the bank’s customers not covered by this study.